The role of a cytoplasmic loop of MotA in load‐dependent assembly and disassembly dynamics of the MotA/B stator complex in the bacterial flagellar motor. Issue 4 (29th September 2017) - Pourjaberi, Seyedeh Noorolhoda Shajari; Terahara, Naoya; Namba, Keiichi; Minamino, Tohru
Summary: The proton‐driven flagellar motor of Salmonella enterica can accommodate a dozen MotA/B stators in a load‐dependent manner. The C‐terminal periplasmic domain of MotB acts as a structural switch to regulate the number of active stators in the motor in response to load change. The cytoplasmic loop termed MotAC is responsible for the interaction with a rotor protein, FliG. Here, to test if MotAC is responsible for stator assembly around the rotor in a load‐dependent manner, we analyzed the effect of MotAC mutations, M76V, L78W, Y83C, Y83H, I126F, R131L, A145E and E155K, on motor performance over a wide range of external load. All these MotAC mutations reduced the maximum speed of the motor near zero load, suggesting that they reduce the rate of conformational dynamics of MotAC coupled with proton translocation through the MotA/B proton channel. Dissociation of the stators from the rotor by decrease in the load was facilitated by the M76V, Y83H and A145E mutations compared to the wild‐type motor. The E155K mutation reduced the number of active stators in the motor from 10 to 6 under extremely high load. We propose that MotAC is responsible for load‐dependent assembly and disassembly dynamics of the MotA/B stator units. Abstract : MotA and MotB together form a stator complex of the bacterial flagellar motor. The stator complex associates with and dissociates from the motor in a load‐dependent manner. Here we provide evidence suggesting that a cytoplasmic loop of MotA contributes to load‐dependent assembly and disassembly dynamics of the stator complex in the motor.